(untitled) (TAMADDUN NURI JURNALI, 2024)
This article discusses the history of Victorian realist novels, the rise of the novel, the evolution of Victorian realist novels, the characteristics of Victorian realist novels, and the publication of realist novels in newspapers and magazines. In world literature, it is recognized that the history of realistic novels of the Victorian era had a great influence on the development of humanitarian ideas, and that they fully described social life and existing problems in society.